The Japanese Beer Wars: Initiating and Responding to Hypercompetition in New Product Development - Craig, Tim (Organization Science, 1996)
In the mid-1980s, the Japanese beer industry, a stable oligopoly in which competition had traditionally been limited to well understood nonprice dimensions, experienced an outbreak of new product “hypercompetition” which saw a ten-fold increase in the industry's new product introduction rate, produced a major shake-up in firms' competitive positions, and forced firms to transform themselves in fundamental ways in order to compete effectively. Surprisingly, this hyper-competition occurred despite heavy government regulation of the industry. Driving it were a variety of demographic, dietary, social, economic, and distribution trends which affected demand for beer, plus the existence of a major player, Asahi, on the edge of bankruptcy and therefore sufficiently desperate to risk a frontal attack on the industry leader, Kirin. At the firm level, substantial internal change and the building of new organizational capabilities were required both to initiate and respond to hypercompetition. Examining in detail the process and difficulty of overcoming inertia and effecting change within the Asahi and Kirin organizations, two distinct types of hypercompetition-appropriate capabilities are identified. One is specialized capabilities, which allow a firm to compete effectively on the competitive dimension that a particular round of hypercompetition is based on (such as new product development). The other is general capabilities which allow a firm to efficiently carry out the continual recombination and reemployment of resources which a hypercompetitive state, in which shifts in the nature of competition are frequent and continuous, requires. Both types of capabilities are shown to be difficult to build and imitate, and for this reason to be potential sources of sustainable advantage. The paper identifies three broadly defining characteristics of hypercompetition: (1) continuing, nonmarginal change in the nature of competition, (2) required nontrivial organizational change, and (3) significant effects on firm performance and competitive position. Conceptually, it is argued that hypercompetition is Schumpeterian in nature, featuring recurring and fundamental competitive change, but that hypercompetition is most accurately seen as a particular combination of Schumpeterian, Industrial Organization, and Chamberlinian competition, with Schumpeterian instability weakening, but not replacing, the more stable aspects of Industrial Organization and Chamberlinian competition.